1990
DOI: 10.1080/02841859009173055
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Biopsy of Liver Hemangioma

Abstract: The results of 36 consecutive fine-needle aspiration biopsies of liver hemangiomas at two University Hospitals from the years 1981-1988 are described. The sizes of the lcsions were I to 15 cm. Six patients had malignant disease. and liver metastasis was considered possible. In 2 cases the chief complaint was related to liver enlargement, and 28 patients had other abdominal symptoms. The aspiration was performed to confirm a suggested hemangioma in 18 and because of inconclusive findings at imaging in 18 cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…While the accurate distinction between FNH and adenoma, as well as hepatocellular carcinoma, may be difficult, it is essential with regard to the appropriate treatment strategy [6]. Percutaneous liver biopsy often has limited benefit and must be regarded as contraindicated, especially in hypervascular tumors such as hemangioma [7]. …”
Section: Introductionmentioning
confidence: 99%
“…While the accurate distinction between FNH and adenoma, as well as hepatocellular carcinoma, may be difficult, it is essential with regard to the appropriate treatment strategy [6]. Percutaneous liver biopsy often has limited benefit and must be regarded as contraindicated, especially in hypervascular tumors such as hemangioma [7]. …”
Section: Introductionmentioning
confidence: 99%
“…11,15,27,56 However, recent studies have shown that fine needle aspiration, as well as 18-gauge core needle biopsy of hepatic vascular tumors, is a safe procedure when care is taken to interpose normal liver tissue between the capsule and the lesion. 3,10,25,36,54,55 The exfoliative and aspiration cytologic features of malignant vascular tumors have been described, mostly as case reports, under various terminologies, including angiosarcoma, angioendothelioma, hemangiosarcoma and hemangioendothelioma. 1,4,8,9,12,19,[21][22][23][30][31][32]34,35,37,[39][40][41][42][46][47][48]50,52,60 The previously reported cytologic features of angiosarcomas are highly variable and have included: low to high cellularity, rare to abundant single cells, binucleated cells, cohesive cell groups, amorphous acellular cores, prominent nucleoli, hyperchromasia, perinuclear halos, absence or presence of hemosiderin, vacuolated cytoplasm with microvesicles and macrovesicles, signet-ring-like cells, erythrophagocytosis, myxoid matrix, necrosis, hemorrhagic background and background neutrophils.…”
Section: Small Nucleoli Were Identified In Five Casesmentioning
confidence: 99%
“…Because improved CT and MRI scanning techniques have evolved, scanning with technetium-labeled erythrocytes has been used less extensively in recent years. Core biopsy and fine-needle aspiration are reportedly safe but may be associated with pain or bleeding and are not recommended for diagnosis [17,18]. From the literature and from our experience, surgical treatment is performed to relieve symptoms of the hemangioma and to treat complications such as severe abdominal pain and distension, thrombocytopenia, hemorrhage, jaundice, and rupture [19,20].…”
Section: Discussionmentioning
confidence: 99%